Evaluation and optimization of material properties of tailor welded Al 6061 alloy and ASS 304 sheets using Taguchi robust design. (2021) - Deepika, D.; Anitha Lakshmi, A.; Srinivasa Rao, Ch.; Sateesh, N.; Nookaraju, B. Ch.; Subbiah, Ram
Abstract: Aluminium alloy 6061-T6 and Stainless ASS 304 are used in present study. The friction stir welding is used in this process to join the base metals. The uniaxial tensile testing procedure parameters, Orientation, Temperature, Strain rate suppose a key job in better Yield strength and % of elongation. The temperature (27 °C, 350 °C, 500 °C), Orientation (R0, R45, R90) to the rolling direction, strain rate (0.1, 0.01, 0.001) S −1 were taken. The L9 orthogonal Taguchi method was utilized to know the impact of procedure parameter on each factor.